Análise da utilização de métodos ágeis no desenvolvimento de ambientes virtuais de aprendizagem: um estudo de caso do Solar 2.0 - Torres Filho, Ari do Amaral (2014)
In the last two decades there has been considerable progress in the use of Information Technologies and Digital Communication in the process of teaching and learning, both in the form of classroom education as distance. In this context, the use of Virtual Learning Environments - software designed to support the courses via the Internet - is growing and access becoming increasingly diverse, ranging from desktop computers to mobile smartphones. Thus, the complexity of creating these environments becomes increasingly technical and requires Software Engineering and Project Management always better to ensure product quality and customer satisfaction generated. Given such a scenario, this paper proposes the use of Agile methodologies in the development and project management of virtual environments as a more interesting way than traditional software delivery based only on product quality, forgetting often , customer satisfaction and motivation of developers. This paper reports the adoption of agile methodologies in the development of the SOLAR AVA 2.0, showing that it is possible to succeed in both the technical level and at the organizational and personally with the adoption of agile practices in the development of AVAs that can be proven through experiments done with the satisfaction surveys with users and project developers.